STRATEGI BERTAHAN HIDUP TUKANG PIJAT TUNANTRA DIKOTA PEKANBARU - Juliana "; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study conducted in the city of pekanbaru. The purpose of this research is to find out how a survival strategi in the city tunanetra masseur pekanbaru with limitions and amid rampant massage places that are emerging so that researchers interested in researching about survival strategies masseur tunantra city of pekanbaru special topic of this research is how the city of the blind masseur profil pekanbaru. Capital of what used to retain customers and how survival strategies masseur bilind in the city of pekanbaru. This research sample is blind masseur who opened the practice of massaging the city of pekanbaru. This research uses descriptive qualitative technique. Data analysis used in this study is method of a single case in question. Data instrument is observation, interview, and documentation. The results of this study indicate that the survival strategies life is blind masseur biological investment strategy, strategy of successive, educational strategies, and economic investment strategiesKeywords: Capital, Strategy, Blind Masseur